Normative Indicators Combining Poverty and Mortality : A Survey - Decerf, Benoit (World Bank, Washington, DC, 2022)
This paper surveys the small branch of welfare economics that studies indicators combining poverty and mortality. The paper distinguishes two reasons for constructing such indicators. The first reason is to perform multidimensional well-being comparisons. For this purpose, mortality has (negative) intrinsic value. The key question relates to the trade-off that the indicator makes between poverty and mortality, that is, between the quality and quantity of life. A lifecycle utility approach suggests expressing this trade-off as the number of years spent in poverty that is deemed equivalent to one year lost to mortality. The second reason is to investigate the instrumental role that selective mortality—the fact that the poor tend to die earlier—has on the evolution of poverty measures. Then, the key question is how to define the counterfactual situation against which the instrumental impact of mortality is assessed.